A COMPARETIVE PHARMACEUTICO CLINICAL STUDY OF KAISORE GUGGULU AND AMRUTADI GUGGULU ON VATARAKTA (International Journal of Ayurveda and Pharma Research, 2017)
Ayurveda, the science of life helps in the management of diseases through its various branches among which Rasashastra is Ayurvedic pharmaceutics, which deals with the drugs of mineral origin, their varieties, characteristics, processing techniques, properties and their therapeutic uses. Formulation in the proposed study two different Guggulu preparations Kaisore Guggulu and Amrutadi Guggulu has been selected whose indications are for Vatarakta apart from other diseases. In the day to day practice the physicians of Ayurvedic fraternity of Odisha use these two medicines in the treatment of Vatarakta. Its incident is said to be 0.2 - 0.3 among the world population and its curability is still apprehensive in remedial field.This is study with comparison by a known standard drugs, carried out on 60 number of patients suffering from Vatarakta Will be selected from the OPD/IPD of Gopabandhu Ayurveda Mahavidyalaya and Hospital, Puri. An overall clinical implement and statistical assessment are also witnessed in favour of trial drugs in a significant manner. Correction in laboratory investigation is also another beneficent favour of drug appended. The question of acceptability of the trial drugs for the treatment of Vatarakta is no more remains apprehended rather it can be safely used for the purpose. From the observation of my study it is found that both the drugs are effective in reducing the sign and symptoms of Vatarakta but while coming to the comparison Amrutadi Guggulu is more effective than the Kaisora Guggulu in the present study.